Patient with neuroblastoma complicated by giant thrombus of an inferior vena cava with intracardiac extension - Bakhram Zhumadullayev; Ainur Akhmetkaliyeva; Anzhelika Meiramova; Saniya Baiturova (National Scientific Medical Center, 2017)
In this article, we presented a rare case of neuroblastoma complicated by giant thrombus of an inferior vena cava with intracardiac extension in a 3 years old child.